Sleep–Wake Cycle in Young and Older Mice - Soltani, Sara; Chauvette, Sylvain; Bukhtiyarova, Olga; Lina, Jean-Marc; Dubé, Jonathan; Seigneur, Josée; Carrier, Julie; Timofeev, Igor (Frontiers in Systems Neuroscience, 2019)
Sleep plays a key role in multiple cognitive functions and sleep pattern changes with aging. Human studies revealed that aging decreases sleep efficiency and reduces the total sleep time, the time spent in slow-wave sleep (SWS), and the delta power (1-4 Hz) during sleep; however, some studies of sleep and aging in mice reported opposing results. The aim of our work is to estimate how features of sleep-wake state in mice during aging could correspond to age-dependent changes observed in human. In this study we investigated the sleep/wake cycle in young (3 months old) and older (12 months old) C57BL/6 mice using local-field potentials (LFP). We found that older adult mice sleep more than young ones but only during the dark phase of sleep-wake cycle. Sleep fragmentation and sleep during the active phase (dark phase of cycle), homologous to naps, were higher in older mice. Older mice show a higher delta power in frontal cortex, which was accompanied with similar trend for age differences in slow wave density. We also investigated regional specificity of sleep-wake electrographic activities and found that globally posterior regions of the cortex show more REM sleep whereas somatosensory cortex displays more often SWS patterns. Our results indicate that the effects of aging on the sleep-wake activities in mice occur mainly during the dark phase and the electrode location strongly influence the state detection. Despite some differences in sleep-wake cycle during aging between human and mice, some features of mice sleep share similarity with human sleep during aging.